Differential regulation of the expression of two high-affinity sulfate transporters, SULTR1.1 and SULTR1.2, in Arabidopsis - Rouached, Hatem; Wirtz, Markus; Hell, Rüdiger (Plant physiology, 2008)
The molecular mechanisms regulating the initial uptake of inorganic sulfate in plants are still largely unknown. The current model for the regulation of sulfate uptake and assimilation attributes positive and negative regulatory roles to O-acetyl-serine (O-acetyl-Ser) and glutathione, respectively. This model seems to suffer from exceptions and it has not yet been clearly validated whether intracellular O-acetyl-Ser and glutathione levels have impacts on regulation. The transcript level of the two high-affinity sulfate transporters SULTR1.1 and SULTR1.2 responsible for sulfate uptake from the soil solution was compared to the intracellular contents of O-acetyl-Ser, glutathione, and sulfate in roots of plants submitted to a wide diversity of experimental conditions. SULTR1.1 and SULTR1.2 were differentially expressed and neither of the genes was regulated in accordance with the current model. The SULTR1.1 transcript level was mainly altered in response to the sulfur-related treatments. Split-root experiments show that the expression of SULTR1.1 is locally regulated in response to sulfate starvation. In contrast, accumulation of SULTR1.2 transcripts appeared to be mainly related to metabolic demand and is controlled by photoperiod. On the basis of the new molecular insights provided in this study, we suggest that the expression of the two transporters depends on different regulatory networks. We hypothesize that interplay between SULTR1.1 and SULTR1.2 transporters could be an important mechanism to regulate sulfate content in the roots.